Surface Electromyography-Driven Therapeutic Gaming for Rehabilitation of Upper Extremity Weakness: A Pilot Study. Issue 1 (10th May 2022) - Liu, Yusha; Silva, Rafael M. L.; Friedrich, Jeffrey B.; Kao, Dennis S.; Mourad, Pierre D.; Bunnell, Aaron E.
Abstract : Summary: In patients with severe upper extremity weakness that may result from peripheral nerve injuries, stroke, and spinal cord injuries, standard therapy in the earliest stages of recovery consists primarily of passive rather than active exercises. Adherence to prescribed therapy may be poor, which may contribute to suboptimal functional outcomes. The authors have developed and integrated a custom surface electromyography device with a video game to create an interactive, biofeedback-based therapeutic gaming platform. Sensitivity of the authors' custom surface electromyography device was evaluated with simultaneous needle electromyography recordings. Testing of this therapeutic gaming platform was conducted with a single 30-minute gameplay session in 19 patients with a history of peripheral nerve injury, stroke, spinal cord injury, and direct upper extremity trauma, including 11 patients who had undergone nerve and/or tendon transfers. The device was highly sensitive in detecting low levels of voluntary muscle activation and was used with 10 distinct muscles of the arm, forearm, and hand. Nerve and tendon transfer patients successfully activated the donor nerve/muscle and elicited the desired movement to engage in gameplay. On surveys of acceptability and usability, patients felt the system was enjoyable, motivating, fun, and easy to use, and their hand therapists expressed similar enthusiasm. Surface electromyography-based therapeutic gaming is a promising approach to rehabilitation that warrants further development and investigation to examine its potential efficacy, not only for building muscle strength and endurance but also for facilitating motor relearning after nerve and tendon transfer surgical procedures. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.